The Study the Effect of Ultraviolet on the Compression and Hardness Property for Hybrid Material - Abbas, R. A. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study was carried out by reinforcing the resin matrix material which was (Epoxy- Ep828) by useing Kevlar fibers and glass fibers type (E-gl ass) both or them in the form of woven roving and poly propylene tlbcrs in the form chopped strand mats. wi th (30%) volume fraction. Some mechan i cal properties of the were prepared composite specimens U ltraviolet radiation were stuied after being subjected to different weathering conditi ons i ncluded. Compression and hardness testing were carried out using Briel! method so as to compare between composite behavior i n the environments previously mentioned .